Climate Change Is Likely to Alter Future Wolf – Moose – Forest Interactions at Isle Royale National Park, United States - De Jager, Nathan R.; Rohweder, Jason J.; Duveneck, Matthew J. (Frontiers in Ecology and Evolution, 2020)
We evaluated how climate change and variable rates of moose browsing intensity, as they relate to wolf predation, might impact the forests of Isle Royale National Park, MI USA by conducting a simulation modelling experiment. The experiment consisted of contrasting three different scenarios of wolf management and with a static (current conditions) and changing climate (high emissions). Our results suggest that the interactive effects of wolf predation and climate change are likely to be temporally variable and dependent on biogeographic and forest successional processes. During the first 50 years of simulations, when the effects of climate change were minor, higher simulated rates of predation by wolves reduced moose population densities, resulting in greater forest biomass and higher carrying capacities for moose. However, over the longer term, early successional and highly palatable aspen and birch forests transitioned to late successional spruce and fir forests, regardless of climate or predation intensity. After 50 years, the effects of climate change and predation were driven by effects on balsam fir, a late successional species that is highly palatable to moose. High-intensity predation of moose allowed balsam fir to persist over the long term but only under the current climate scenario. Climate change caused a reduction in balsam fir and the other boreal species that moose currently feed on, and the few temperate species found on this isolated island were unable to compensate for such reductions, causing strong declines in total forest biomass. The direct effects of moose population management via reintroduction of wolves may become increasingly ineffective as the climate continues to warm because the productivity of boreal plant species may not be sufficient to support a moose population at all, and the isolation of the island from mainland temperate tree species may reduce the likelihood of compensatory species migrations.